Polish ethnocultural rural landscapes of Podillya - ВОЛОВИК, В. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
In the article the features of the structure of the Polish ethnocultural rural landscapes of Podillya. Dedicated general laws of formation of these landscapes, their ethnocultural features and characteristics of management. Indicated the presence of «core» in a residential part – «estates», of the landscape – «garden and park landscape complex» and peripherals – «folwark». Analyzed historical and cultural characteristics of ethnocultural formation of rural landscapes XVII – early XX century. For example Dobrovolsky estate in the village Fedorivka Sharhorod region’s Vinnytsia oblast reveals the current state of nature and characteristics of Polish rural ethnocultural landscape; created landscape map. Emphasized the superiority of an interdisciplinary approach, taking into account the achievements of physical geography, history, ethnology, geopolitics, social and economic geographies.